Dualitas Konstitusional: Tinjauan Yuridis Konsep Velayat-E Faqih Terhadap Praktik Republikanisme Di Iran - Andi Ardiansyah; Kurniati . (CV. ITTC INDONESIA, 2026)
This study aims to analyze the constitutional paradox in the Islamic Republic of Iran following the 1989 Constitutional Amendment. The research focuses on the conceptual and practical tension between the doctrine of Velayat-e Faqih (Guardianship of the Islamic Jurist), which embodies the principle of divine sovereignty, and the republican principle based on popular sovereignty. This study employs a normative legal research method with a qualitative approach through conceptual, historical, and comparative analyses. The analysis examines constitutional provisions and the distribution of authority among state institutions to identify the dynamics of power within Iran's constitutional system. The findings indicate that non-elective institutions, particularly the Guardian Council and the Supreme Leader, possess constitutionally entrenched powers that significantly constrain the independence of elective institutions, including the President and the Majles (Parliament). These findings demonstrate that the conventional Western doctrine of checks and balances is insufficient to explain the hybrid and asymmetrical nature of Iran's constitutional governance. Accordingly, this study proposes the concept of Concurring Constitutionalism as an alternative constitutional paradigm aimed at fostering a more balanced distribution of state power while preserving both the Islamic identity of the state and the political rights of its citizens.